The Concept of Privacy in the International Information Relations and its Development by International Judicial Institutions - TALIMONCHIK, Valentina Petrovna; MARUSIN, Igor Stanislavovich; BAKHIN, Sergei Vladimirovich (Journal of Advanced Research in Law and Economics; Vol 9 No 3(33) (2018): JARLE, Volume IX, Issue 3(33), Summer 2018, 2018)
The aim of the research is to identify the content of the concept of privacy in the sphere of information developed at the universal and regional levels and the directions of its development by international judicial institutions. A complex of general scientific and philosophical methods, including the logical, comparative-legal, formal-legal, systemic-structural, problematic-theoretical methods, as well as methods of analysis and synthesis, generalization and description, comparison were used in the research. As a result of the research, it was identified that a unified concept of privacy has been formed in the sphere of information at the universal and regional levels. This concept was developed in acts of international judicial institutions that limited the privacy of political and public figures and extended the requirement of privacy protection to the relations on the Internet. The findings can be used in the activities of international organizations in execution of their functions of unification and harmonization of the international information law and by national courts in the implementation of international law.